Improving Database Quality by Applying Consistency Aspects to Naming Fields and Tables - Raissa Maringka; Aulia Khoirunnita; Rodney Maringka; Ema Utami; Kusnawi (TEPIAN, 2021)
The database is one of the benchmarks that affect the quality of information systems. An effective information system certainly has a quality database. Aspects that can be measured to determine the quality of the database are aspects of truth, consistency, range, level of detail, completeness, minimalism, ability to integrate and readability. One of the mistakes that are often encountered in databases is related to the consistency aspect. Consistency aspects that are not paid much attention to its application can lead to data conflicts due to ambiguity and data duplication. This study aims to improve the quality of the database by applying consistency to the naming of fields and tables. A naming method to produce consistency in standardization was applied in this study.